The Ethnobotany of Abui’s Home Gardens and its Potentiality to Support Rural Tourism Development in Alor, Indonesia - Isak Feridikson Alelang; Luchman Hakim; Jati Batoro (Program Pascasarjana, 2018)
The aim of the research is to explore the value of home gardens at Abui community in Takpala Village, Alor Island,Â a basis rural of rural tourism development. The value of home gardens was assessed in the perspective local people culture and perspectives. Therefore, ethnobotanical assessment using Important Cultural Value (ICS) index was implemented. Data was collected through field observation and interviews to local community. Survey was done in 15 house in Takpala settlements by identifying plant species in home gardens area. Interviews were performed to generate information regarding flora benefits in the daily life of local people in Takpala. Result of the study shows that homegarden has an important role among Abui community, especially in cultivating numerous plant species for daily life. Home garden has its potentiality to introduced as part of the tourism development attraction in Takpala Village.Keywords: conservation, economic plant, rural tourism, Timor home garden.